Audit Tata Kelola Teknologi Informasi Domain Monitor, Evaluate, and Asses dan Deliver, Service, Support Berdasarkan Framework COBIT 2019 - Ike Pertiwi Windasari; Adian Fatchur Rochim; Septi Nurna Alfiani; Azizah Kamalia (Universitas Diponegoro, 2021)
University is a form of tertiary institution that has a tridharma task to assist the government in handling and implementing development in all fields, especially education. Information technology and information systems tools are important to support the achievement of the university's vision and mission. University information technology governance is an activity used to measure existing information technology to support the achievement of university activity goals. The obstacle faced by the university is that every year it spends a large budget with activities related to information technology (IT) ranging from design, implementation, IT training for the entire academic community, but the results obtained cannot be measured. This research was conducted to measure the maturity of IT implementation at universities. In this study, using COBIT 2019 as a framework on the two domains of MEA and DSS in the research object university (PTOP). Two of these domains are expected to be able to measure the target Capability Level, Capability Level current and gaps (gap) The data source used is the results of interviews with IT governance authorities. The research object case study at one of the universities in Semarang, hereinafter referred to as the research object college (PTOP). Based on the research results, it was found that the PTOP capability level in the MEA and DSS domains was at level 1 or performed, which means that the process carried out had more or less reached the goal, but through the implementation of a series of activities that were less organized.